Risk of advanced colorectal neoplasm in patients with more than 10 adenomas on index colonoscopy: A Korean Association for the Study of Intestinal Diseases (KASID) study. Issue 4 (April 2017) - Park, Soo‐Kyung; Hwang, Sung Wook; Kim, Kyeong Ok; Cha, Jae Myung; Boo, Sun‐Jin; Shin, Jeong Eun; Joo, Young‐Eun; Jung, Yunho; Lee, Jun; Yang, Hyo‐Joon; Park, Dong Il; ,
Abstract: Background and Aim: The number of patients with >10 adenomas is relatively small, and few studies have investigated the risk of colorectal neoplasm (CRN) in these patients. Thus, we aimed to investigate the risk of developing CRN in patients with >10 adenomas and to compare their risk with that of patients with 3–10 adenomas. Methods: A retrospective multicenter cohort study that included 214 patients with >10 adenomas on index colonoscopy performed between January 2009 and December 2011, and underwent follow‐up colonoscopy until December 2015 was conducted. The risk of developing advanced CRN (cancer or advanced adenoma with a diameter of ≥10 mm or with a villous component, or high‐grade dysplasia) was investigated and compared with that in patients with 3–10 adenomas ( n = 975). Results: Among the 214 patients with >10 adenomas, the mean age was 62.9 years and the mean number of adenomas on index colonoscopy was 14.2. Overall, 57 patients (26.6%) developed an advanced CRN after a mean of 4.3 years from baseline colonoscopy. The respective 3‐ and 5‐year cumulative risks of advanced CRN were 6.8% (95% confidence interval [CI] 2.9–10.7) and 28.7% (95% CI 20.8–36.5), higher than those in the group with 3–10 adenomas ( n = 975, P = 0.001). Having >10 adenomas on index colonoscopy was an independent risk factor for developing advanced CRN (odds ratio 2.25, 95% CI 1.49–3.38). Conclusions: The risk of developing advanced CRN in patients with >10 adenomas was high and statistically higher than that in patients with 3–10 adenomas. Further prospective studies are needed to investigate whether a more intensive surveillance is needed in this group.